2020
DOI: 10.1101/2020.03.22.20040600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human leukocyte antigen susceptibility map for SARS-CoV-2

Abstract: We probe how genetic variability across the three major histocompatibility complex (MHC) class I genes (human leukocyte antigen [HLA] A, B, and C) may affect susceptibility to and severity of severe acute respiratory syndrome 2 (SARS-CoV-2), the virus responsible for coronavirus disease 2019 (COVID-19). We execute a comprehensive in silico analysis of viral peptide-MHC class I binding affinity across all known HLA -A, -B, and -C genotypes for all SARS-CoV-2 peptides. We further explore the potential for cross-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
147
2
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 77 publications
10
147
2
6
Order By: Relevance
“…Moreover, very little is understood about interindividual genetic differences in the immune response to this new and novel version of the old coronavirus. A possible association between the genetic variability in histocompatibility complex (MHC) class I genes (human leukocyte antigen [HLA] A, B, and C) and the susceptibility to SARS-CoV-2 and severity of COVID-19 has recently been suggested [9]. Specifically, the HLA-B*46:01 gene product is predicted to exhibit the lowest binding capacity to SARS-CoV-2 peptides, suggesting individuals with this allele may be more vulnerable to COVID-19-due to reduced capacity for viral antigen presentation to immune cells.…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, very little is understood about interindividual genetic differences in the immune response to this new and novel version of the old coronavirus. A possible association between the genetic variability in histocompatibility complex (MHC) class I genes (human leukocyte antigen [HLA] A, B, and C) and the susceptibility to SARS-CoV-2 and severity of COVID-19 has recently been suggested [9]. Specifically, the HLA-B*46:01 gene product is predicted to exhibit the lowest binding capacity to SARS-CoV-2 peptides, suggesting individuals with this allele may be more vulnerable to COVID-19-due to reduced capacity for viral antigen presentation to immune cells.…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
“…Specifically, the HLA-B*46:01 gene product is predicted to exhibit the lowest binding capacity to SARS-CoV-2 peptides, suggesting individuals with this allele may be more vulnerable to COVID-19-due to reduced capacity for viral antigen presentation to immune cells. Conversely, the authors identified that the HLA-B*15:03encoded protein is predicted to have the greatest capacity to present highly conserved SARS-CoV-2 peptides that are shared among common human coronaviruses [9]-suggesting patients possessing this HLA genotype may be more likely to develop immunity. Finally, during some viral infections (including HIV), the ADF/cofilin complex (ADF, actin-depolymerizing factor, is encoded by the DSTN gene; cofilin is encoded by CFL1 and CFL2 genes) is activated.…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
“…These features confer unique properties to the epitope maps that underlie our epitope hotspot predictions and digital twin optimization. These properties differ from the SARS-CoV-2 epitope maps that have been reported in recent preprints since the outbreak of this virus, which mainly utilize predictions based on HLA binding [29][30][31].…”
Section: Resultsmentioning
confidence: 86%
“…Taken together, this supports the approach taken in this study, which is to map computationally, a broad epitope landscape across the global viral SARS-CoV-2 proteome, which includes integrated CD8, CD4 and B cell targets in the modeling. There has been some preliminary efforts submitted into preprint servers recently that describe epitope maps generated [29][30][31], however it appears that the emphasis in those approaches were based mostly on HLA binding. It is important to profile in whole viral proteome epitope screens, as carried out in this study using an extensive artificial intelligence platform, not only the candidates that may bind to the HLA molecule but also those CD8 epitopes that are naturally processed by the cell's antigen processing machinery, and presented on the surface of the infected host cells.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Surprisingly, a recent in silico analysis of viral peptide-HLA interaction that awaits publication suggests that the HLA-B*46:01 allele could also impact the severity of COVID-19 and that the HLA-B*15:03 allele could confer immunity to the disease. 10 Vaccination policies between countries could be an important factor in susceptibility or protection against COVID-19. For example, it has been reported that the Bacillus Calmette-Guerin (commonly referred to as BCG) vaccine may confer protection against respiratory infections.…”
mentioning
confidence: 99%